2017
DOI: 10.21873/anticanres.11488
|View full text |Cite
|
Sign up to set email alerts
|

Differing Mechanisms of Death Induction by Fluorinated Taxane SB-T-12854 in Breast Cancer Cells

Abstract: Cell death induced by SB-T-12854, in the tested breast cancer cells, differs regarding activation of caspases, changes in levels of pro-apoptotic and anti-apoptotic proteins of the Bcl-2 family and activation of the mitochondrial apoptotic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Therefore, it is possible that presence of ERα may amplify p53 stability and increased activation of p53 may sensitize cells to apoptotic signaling in BOK-silenced MCF7 cells. Furthermore, differences in expression of Bcl-2 family proteins and lack of functional caspase-3 in MCF7 cells [ 27 ] may also contribute to reduce long-term viability of BOK-silenced MCF7 cells compared to MDA-MB-231 or MDA-MB-468 cells. Nevertheless, depletion of both BOK and Mcl-1 rescued the effect of Mcl-1 silencing on long-term viability of MDA-MB-231, MDA-MB-468 and MCF7 breast cancer cells (Figure 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is possible that presence of ERα may amplify p53 stability and increased activation of p53 may sensitize cells to apoptotic signaling in BOK-silenced MCF7 cells. Furthermore, differences in expression of Bcl-2 family proteins and lack of functional caspase-3 in MCF7 cells [ 27 ] may also contribute to reduce long-term viability of BOK-silenced MCF7 cells compared to MDA-MB-231 or MDA-MB-468 cells. Nevertheless, depletion of both BOK and Mcl-1 rescued the effect of Mcl-1 silencing on long-term viability of MDA-MB-231, MDA-MB-468 and MCF7 breast cancer cells (Figure 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been indicated that next-generation taxoids, exhibiting high potencies against CSCs, suppress the expression of “stemness genes”, promoting differentiation of the treated CSCs (Figure ), which may provide a new mechanism of action for taxoid anticancer agents for which the major MOA is the blocking of cell mitosis at the G2/M stage, leading to the activation of caspases and then apoptosis. ,, …”
Section: Newer Insights Into the Mechanism Of Actionmentioning
confidence: 99%